«Today we need to talk about the Civil War with restraint, without the desire to take anyone’s side...» - R. G. Gagkuev (Омский научный вестник: Серия "Общество. История. Современность")
Ruslan Grigorievich Gagkuev — Doctor of Historical Sciences, Chairman of the Board of the Russian Historical Society, Executive Director of the History of the Fatherland Foundation, leading researcher at the Center for Military History of Russia at the Institute of Russian History of the Russian Academy of Sciences. Wellknown researcher of the history of the Civil War in Russia. Ruslan Grigorievich visited Omsk several times on scientific affairs. This interview was agreed upon during the preparation of the V International Scientific and Practical Conference «Civil War in the East of Russia: A Look Through the Documentary Heritage». The interview was given remotely and then edited by Ruslan Grigorievich from Moscow in October 2023. The conversation is devoted to the current state of the study of the Civil War in Russia and the development of domestic historical science.